(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of health service utilization and explore associated factors among Indian medical students in Vietnam. Methods: A cross-sectional study was conducted in April 2026 among all first-year Indian medical students at Dai Nam University, Vietnam. Of 192 eligible students, 190 participated (response rate: 99.0%). Data were collected using a structured self-administered questionnaire via Google Forms. Descriptive statistics were used to summarize the data, and Chi-square tests were applied to examine associations between variables and health service utilization. Results: Most participants reported good or fair self-rated health (79.48%), and the prevalence of chronic diseases was low (6.84%). Health-related behaviors were generally positive, with 97.37% being non-smokers, 94.21% reporting no alcohol consumption, and 88.42% engaging in physical activity at least once per week. Only 24.74% of students reported using health services in the past 12 months. Among service users, private clinics or hospitals were the most utilized (42.55%), followed by public hospitals (36.17%). Acute illness was the leading reason for healthcare utilization (42.55%). No statistically significant factors associated with health service utilization were identified (p > 0.05). Conclusion: Indian medical students in Vietnam demonstrated relatively good health status and positive health behaviors; however, health service utilization remained low. Strategies to promote access to healthcare services, particularly preventive and mental health services, for international students are needed.